Clean And Healthy Living Behaviour Education With The Manufacture Of Oralit Solution As A Dehydration Prevention - Irfan Darfika Lubis; Indira Fitriani; Indah Putri Salsabilla; Salsabillah Siregar; Bassyar Al Az; Vinola Dwi Maulana (Buletin Farmatera, 2026)
Abstract: Diarrhoea is one of the health problems that often occurs in school-age children and can cause dehydration if not treated properly. The implementation of Clean and Healthy Living Behaviour (PHBS) and providing education on the manufacture of simple oralit solution is an effective preventive effort to increase the awareness and skills of students. This activity was carried out in the context of community service activities on August 20, 2025, at SMPN 3 Kutalimbaru Satu Atap, Namo Rube Julu Village, Kutalimbaru District, Deli Serdang Regency, North Sumatra Province, involving 30 students. The method used is in the form of interactive counselling about PHBS through banner media, discussions, and quizzes, which is then followed by making an oralit solution using simple ingredients such as sugar, salt, and water. The results of the activity showed an increase in students' understanding of the importance of maintaining personal hygiene, food, and the environment, as well as skills in making oral rehydration solution as a first aid for dehydration. This activity received a positive response from the participants, even though there were still obstacles in the form of limited time and sanitation facilities. Overall, PHBS education accompanied by the practice of making oral hygiene is proven to increase the knowledge and awareness of students, so it is expected to be able to become a habit that is applied consistently both at school and at home.